(untitled) (CIPEEX, 2025)
Quality of life (QoL) has been much discussed, especially among professionals in the public sector, due to the increased demand for services, especially during and after the COVID-19 pandemic. Seeking to maintain the QoL of public servants is essential not only for their personal well-being, but also to ensure efficiency and effectiveness in the workplace. The World Health Organization defines the term QoL as an individual’s interpretation of their position in life, in a cultural context, the values that guide them, goals, expectations, criteria and concerns. However, despite the importance of QoL, there is controversy about its meaning and what should be measured, as it is a complex concept that can be interpreted in various ways. Some of the most important factors affecting QoL are physical and psychological well-being. Although there are many studies that discuss QoL, many are directed at specific positions, and in the literature, there are few that emphasize the importance of delving into aspects that involve the QoL of civil servants in a comprehensive way. Therefore, this study aims to analyze factors that influence the QoL of civil servants, using as its research method a bibliographic review of articles published in the Web of Science, Scopus, PubMed and Virtual Health Library of the Ministry of Health (VHL) databases. The inclusion criteria involved articles published in English, studies that assessed QoL, free access and the full availability of articles published between 2019 and 2024. As a search strategy, three blocks of words were used, related to the following terms: “Quality of life”, “Public sector” and “Public servant”. Duplicate articles, opinion pieces, commentaries and case reports were removed, resulting in a final analysis of 10 full articles. The analysis of these studies reveals that the work environment has a major influence on the QoL of individuals, from the moment that organizations in search of professional improvement and training to deal with the current demands of society, prioritize large-scale production, maintaining quality with the minimum of necessary resources. When methods are not implemented to minimize the causes that affect the QoL of civil servants, this scenario can worsen, leading to an increase in chronic non-communicable diseases such as hypertension, diabetes, cardiovascular diseases and mental disorders such as depression and anxiety. It is inconsistent to speed up processes if there is a drop in the quality of services and a negative impact on the health of civil servants. Ensuring a healthy environment in order to prevent people from becoming ill will have a beneficial effect on the productivity and QoL of civil servants. Thus, by adopting effective measures that promote greater satisfaction among civil servants, the quality of the services offered can be improved.